Local Wisdom-Based English Language Learning Model to Enhance Students' Literacy Skills and Cultural Awareness - Yuni Wulandari; Dea Okviar Egano Napitupulu; Wahyu Hidayat (Universitas Islam Negeri Sumatera Utara, 2026)
This study aimed to analyze the effectiveness of a local wisdom-based English language learning model in enhancing junior high school students' literacy skills and cultural awareness. The study was motivated by the need to improve students' reading literacy while strengthening their understanding of local culture in English learning. This research employed a quantitative approach with a quasi-experimental pretest-posttest control group design. The sample consisted of 60 grade VIII students who were selected through purposive sampling and divided into an experimental group and a control group. The experimental group received English learning activities integrating folklore, traditional poetry, local traditions, and community culture, while the control group received conventional learning. Data were collected using literacy tests, cultural awareness questionnaires, observation sheets, and documentation. The data were analyzed using normality and homogeneity tests, independent sample t-tests, and N-Gain analysis. The results showed that the local wisdom-based English language learning model increased students' literacy skills with an N-Gain score of 0.71 in the high category and cultural awareness with an N-Gain score of 0.68 in the moderate-high category. These findings indicate that contextual learning materials rooted in students' local culture can create meaningful learning experiences, improve engagement, and strengthen students' cultural identity. Therefore, the model is effective and relevant for English language learning that integrates literacy development and cultural preservation.